Schwartz-jampel syndrome: report of five cases - Umbertina Conti Reed; Rubens Reimão; Adriana Ávila Espíndola; Fernando Kok; Lúcio Gobbo Ferreira; Maria Bernardete Dutra Resende; Thelma Correia Messias; Mary Souza Carvalho; Aron Diament; Milberto Scaff; Suely Kazue Nagahashi Marie (Arquivos de Neuro-Psiquiatria)
We describe five patients with Schwartz-Jampel syndrome (SJS) examined at the outpatient service for neuromuscular disorders at our Institution from 1996 to 1999 with the objective of emphasizing the characteristic dysmorphic phenotype of SJS and its different clinical forms. Two cases presented SJS-type 1A, two had SJS-type 1B and one manifested SJS-type 2. Two boys with 3 and 13 years of age had generalized stiffness and the characteristic facial as well as osteoarticular changes from birth. Other two boys with 11 and 7 years had less marked dysmorphic changes at birth and manifested myotonia, as a limiting factor, during the second year of age. A girl with two months of age had severe myotonia from birth leading to feeding diffuculties. In all cases the diagnosis was based on dysmorphic features, and on electromyographic changes showing continuous electrical activity of muscle fibers. All were treated with carbamazepine, 20-30 mg/Kg since diagnosis. The four boys (all with normal intelligence) improved of myotonia in daily activities, markedly in three, and moderately in one. The girl did not improve and showed global development delay: by the last follow-up (at 20 months of age) she did not sit unsupported, and had mental retardation. Carbamazepine in SJS-type 1 improves general daily performance and psychological status of the patients.